Analisis Yuridis Terhadap Putusan Hakim Dalam Perkara Tindak Pidana Dan Larangan Penggunaan Bahan Kimia - Nadya Chairani; Madiasa Ablisar; Marlina Marlina; Wessy Trisna (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
This research examines the use of hazardous chemicals as food additives, such as formalin and borax, which have the potential to endanger consumer safety. The District Court Decision Number 100/Pid.B/2022/PN Lgs. regarding the case of the perpetrator, Miswardi Bin Usman, who was found to have used prohibited substances in food production, raises questions about legal regulations, criminal liability, and the enforcement of criminal law. The research method employed is normative legal research with a focus on literature analysis, particularly the Decision Number 100/Pid.B/2022/PN Lgs. The research results indicate that the decision raises concerns regarding legal justice, particularly concerning the accountability of the defendant under Article 136 of the Food Law. The judge's decision appears to impose sanctions that are considered too lenient. The research concludes that the judge, as a law enforcement officer, does not seem to fully reflect the principles of a rule of law as mandated by the 1945 Constitution. The decision raises doubts about the effectiveness of law enforcement regarding the use of hazardous chemicals in food. Therefore, a reconsideration of the handling of similar cases is necessary to ensure justice and consumer safety in line with the country's goals as a rule of law